Antioxidant Effects of Potassium Ascorbate with Ribose Therapy in a Case with Prader Willi Syndrome. Issue 4 (21st May 2013) - Anichini, C.; Lotti, F.; Longini, M.; Proietti, F.; Felici, C.; Perrone, S.; Buonocore, G.
Abstract : Oxidative stress (OS) is involved in several human diseases, including obesity, diabetes, atherosclerosis, carcinogenesis, as well as genetic diseases. We previously found that OS occurs in Down Syndrome as well as in Beckwith-Wiedemann Syndrome (BWS). Here we describe the clinical case of a female patient with Prader Willi Syndrome (PWS), a genomic imprinting disorder, characterized by obesity, atherosclerosis and diabetes mellitus type 2, pathologies in which a continuous and important production of free radicals takes place. We verified the presence of OS by measuring a redox biomarkers profile including total hydroperoxides (TH), non protein-bound iron (NPBI), thiols (SH), advanced oxidation protein products (AOPP) and isoprostanes (IPs). Thus we introduced in therapy an antioxidant agent, namely potassium ascorbate with ribose (PAR), in addition to GH therapy and we monitored the redox biomarkers profile for four years. A progressive decrease in OS biomarkers occurred until their normalization. In the meantime a weight loss was observed together with a steady growth in standards for age and sex.